The iterated prisoners' dilemma : 20 years on - Kendall, Graham, 1961- (Advances in natural computation, 2007)
In 1984, Robert Axelrod published a book, relating the story of two competitions which he ran, where invited academics entered strategies for the Iterated Prisoners? Dilemma. The book, almost 20 years on, is still widely read and cited by academics and the general public. As a celebration of that landmark work, we have recreated those competitions to celebrate its 20th anniversary, by again inviting academics to submit prisoners? dilemma strategies. The first of these new competitions was run in July 2004, and the second in April 2005. Iterated Prisoners? Dilemma: 20 Years On essentially provi.